Implementasi Data Analytic Dalam Upaya Peningkatan Penjualan Properti Sebesar 10% Di NYC Amerika Serikat - Fasha I. Husna; Tranggono Tranggono (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
The property industry is an example of an industry that is expected to continue to grow. Problems related to obstacles that occur in property transactions are the decline in the level of property sales in an area. This can happen due to several causes such as infrastructure gaps in each region, lack of promotion, etc. This research will answer the question of how to increase property sales by 10% every year in the New York City area of ​​the United States. The dataset used in this research was taken via the Kaggle website and comes from information on the number of property sales in 5 boroughs in NYC from 2016-2017. It is hoped that the conclusions from the related journals will provide a recommendation model to increase property sales by 10% in the coming year in NYC.